A quantitative model of technological catch-up - Gholizadeh, Hossein; Bonyadi Naeini, Ali; Moini, Alireza (International Journal of Engineering and Technology, 2015)
This article presents a quantitative model for the analysis of technological gap. The rates of development of technological leaders and followers in nanotechnology are expressed in terms of coupled equations. On the basis of this model (first step) comparative technological gap and rate of that will be studied. We can calculate the dynamics of the gap between leader and follower. In the Second step, we estimate the technology gap using the metafrontier approach. Then we test the relationship between the technology gap and the quality of dimensions of the Catch-up technology which were identified in previous step. The usefulness of this approach is then demonstrated in the analysis of the technological gap of nanotechnology in Iran, the leader in Middle East and the world. We shall present the behaviors of the technological leader and followers. At the end, analyzing Iran position will be identified and implying effective dimension of catch-up Suggestions will be offered which could be a fundamental for long-term policies of Iran.